Mengukur Minat Belajar dalam Mencegah Kenaikan Angka Putus Sekolah SD di Lombok - Nurmia, Lidia Zindarti; Munandar, Rizky (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
Measuring learning interest in preventing the increase in dropout rates in Lombok. The current educational problem is that many students no longer have an interest in learning. This study aims to measure learning interest in preventing the increase in elementary school dropout rates in Lombok. This study is a classroom action research by measuring the pre-test and post-test abilities of learning interest indicators. This study was conducted in class V SDN 30 Ampenan with a population of 32 students. The results of the study indicate that it is necessary to increase students' interest in learning, especially students' attention and motivation to learn. Parents and the environment have an important role in increasing elementary school students' interest in learning. In addition, there needs to be an increase in awareness of the importance for elementary school students, this is because many elementary school students are addicted to using cellphones so that it affects their learning outcomes.